Effects of Computer Assisted Instruction on Secondary School Mathematics Students’ Spatial Ability, Achievement and Attitude in Niger State, Nigeria - Ahmadu Hussaini; Gambari Amosa Isiaka; Abdul-Rasaq Olayiola Opeyemi; Alabi Thomas Omotayo (Journal of Education and Learning (EduLearn), 2017)
This study investigated the effect of computer assisted instruction on secondary school mathematics students’ spatial visualization ability, achievement and attitude in Niger State. Three (3) research questions and their corresponding hypotheses guide the study. The study adopted a quasi-experimental design using pretest posttest non-equivalent, non randomized control group. The instruments for data collection were Geometry Achievement Test (GAT), Spatial Ability Test (SAT), and Mathematics and Technology Attitude Scale (MTAS) validated by six senior lecturers. The target population were all SS II mathematics students in the 150 senior Secondary Schools in three educational zones of Niger State. The sample consisted of 330 SS II (178 males and 152 females) from nine secondary schools. In each school, a stream (arm) of SS II class was randomly selected and used for the study. The three groups were pretested using GAT and SAT to determine their entry-level equivalence, while the post-test instruments are SAT and MTAS administered after six (6) weeks of instruction. The finding of the study revealed that the males outperform than females in spatial ability tasks and had higher positive attitude towards learning mathematics with technology. The study recommend mathematics teachers and instructors should adopt modern teaching pedagogies that are learner-centred and provides platform the development of spatial skills in children and adult a likes.